Selective blockade of acid-sensing ion channel 1a can provide substantial hippocampal neuroprotection - Li, Jiaai; Cheng, Yu; Ma, Di; Li, Guangjian; Zhao, Weixuan; Jiang, Ting; Meng, Hongmei (Frontiers in Cell and Developmental Biology, 2025)
BackgroundAcid-sensing ion channel 1a (ASIC1a) is the only member of the ASIC family where Ca2+ osmosis has been reported, and it is highly expressed in neurons of the central nervous system. This study aimed to investigate whether ASIC1a is trafficked to the plasma membrane and regulated by the Rho/ROCK and PI3K signaling pathways in temporal lobe epilepsy (TLE). In addition, further research is required to determine whether selective ASIC1a blockade is a viable therapeutic strategy for TLE.MethodsThe localization and expression levels of ASIC1 and mRNA levels of ASIC1a were detected when the Rho/ROCK and PI3K signaling pathways were activated and inhibited in glutamate (Glu)-induced cell. Meanwhile, we analyzed the location and expression of ASIC1 using Western blotting and immunofluorescence in brain tissue samples from TLE patients, kainic acid (KA)-treated rats, and Glu-induced primary hippocampal neurons. Currently, no specific ASIC1a antibody is available, so the ASIC1 antibody was used in this study, as in previous studies. Furthermore, we evaluated the HT22 cell survival rate, mitochondrial damage, apoptosis, and autophagy to examine whether selective blocking ASIC1a (PcTx1) could play a neuroprotective role.ResultsFirst, the Rho/ROCK and PI3K signaling pathways affect the regulation of the expression and localization of ASIC1, especially the mRNA levels of ASIC1a in the Glu-induced HT22 cell injury model. Second, the high expression of ASIC1 in epilepsy patients was verified in all three sample types, and the phenomenon of its transport from the cytoplasm to the cell membrane/mitochondria was confirmed. Finally, although ASIC1 has a limited epileptogenic effect in the acute phase of epilepsy in vivo, selective blockade of ASIC1a using PcTx1 provided significant hippocampal neuroprotection and reduced mitochondrial damage, apoptosis, and cellular autophagy in vitro.InterpretationThis study is a systematic report concerning ASIC1a in temporal lobe epilepsy, including in vivo and in vitro experiments addressing both the acute and chronic phases. It provides foundational research for proposing ASIC1a as a new target for epilepsy treatment.